2010
DOI: 10.1586/ern.09.154
|View full text |Cite
|
Sign up to set email alerts
|

What is it with the weather and stroke?

Abstract: An influence of climate upon cerebrovascular risk is both biologically plausible and supported by epidemiological evidence. These relationships are important as they could yield public health strategies to help protect the vulnerable from the increased death rates arising during extreme cold and heat waves. Change in temperature impacts on many cerebrovascular risk factors, including serum lipid and fibrinogen concentration and blood pressure. The relationship between stroke and meteorological variables is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 57 publications
(54 reference statements)
5
43
0
Order By: Relevance
“…This study provides helpful results to clarify several discordances among previous studies and supports a recent review, 10 which reported that the influence of climate/weather on cerebrovascular risk is biologically plausible. One of the major contribution to this study derives by the use of an innovative source of meteorologic data (Reanalysis).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study provides helpful results to clarify several discordances among previous studies and supports a recent review, 10 which reported that the influence of climate/weather on cerebrovascular risk is biologically plausible. One of the major contribution to this study derives by the use of an innovative source of meteorologic data (Reanalysis).…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3][4][5][6][7][8][9] Nevertheless, as reported in a recent review, 10 authors often described discordant effects of both air temperature and atmospheric pressure.…”
mentioning
confidence: 99%
“…For example, cold temperature may lead to vasoconstriction to divert blood flow to central vital organs, resulting in a rise in blood pressure. 35 Low outdoor temperature was strongly associated with high blood pressure in Chinese adults across a range of climatic conditions, 36 and hypertension is the most important risk factor for hemorrhagic stroke in China. Cold stress may theoretically increase oxygen demand of the brain, 37 which may in turn induce an excess of cerebral blood flow and exacerbate brain ischemia.…”
Section: Figurementioning
confidence: 99%
“…Dehydration on hot days may also increase blood viscosity and cholesterol levels, which in turn increases the likelihood of microvascular thrombosis and subsequent stroke. 35 Finally, high temperature is associated with worse endothelial function. 39 Further mechanistic studies are warranted to disentangle these complex relationships between ambient temperature and stroke.…”
Section: Figurementioning
confidence: 99%
“…They found that youth reported more symptoms of post-traumatic stress disorder (PTSD). Thus, WHO Regional Office for Europe meeting report on climate change, extreme weather events and public health that was held in Bonn on 29-30 November 2010 highlights a significant impact of an increase of water (a flood) on human life and well-being" (McArthur, Dawson, & Walters, 2010).…”
Section: Source Of Risk Factormentioning
confidence: 99%